Cloning, purification and characterization of a thermostable Î²-galactosidase from Bacillus licheniformis strain KG9 - Matpan Bekler, F; Stougaard, P; Güven, K; Gül Güven, R; Acer, í– (Cellular and Molecular Biology, 2015)
thermo- and alkalitolerant Bacillus licheniformis KG9 isolated from TaÅŸlÄ±dere hot water spring in Batman/Turkey was found to produce a thermostable Î²-galactosidase. Phylogenetic analysis showed that the 16S rRNA gene from B. licheniformis strain KG9 was 99.9% identical to that of the genome sequenced B. licheniformis strain DSM 13. Analysis of the B. licheniformis DSM 13 genomic sequence revealed four putative Î²-galactosidase genes. PCR primers based on the genome sequence of strain DSM 13 were used to isolate the corresponding Î²-galactosidase genes from B. licheniformis strain KG9. The calculated molecular weights of the Î²-galactosidases I, II, III, and IV using sequencing data were 30, 79, 74, and 79 kDa, respectively. The genes were inserted into an expression vector and recombinant Î²-galactosidase was produced in Escherichia coli. Of the four Î²-galactosidase genes identified in strain KG9, three of them were expressed as active, intracellular enzymes in E. coli. One of the recombinant enzymes, Î²-galactosidase III, was purified and characterized. Optimal temperature and pH was determined to be at 60 ºC and pH 6.0, respectively. Km was determined to be 1.3 mM and 13.3 mM with oNPG (ortho-nitrophenyl-Î²-D-galactopyranoside) and lactose as substrates, respectively, and Vmax was measured to 1.96 Î¼mol/min and 1.55 Î¼mol/min with oNPG and lactose, respectively.